A MOF platform for incorporation of complementary organic motifs for CO2 binding1. Issue 62 (11th August 2015) - Deria, Pravas; Li, Song; Zhang, Hongda; Snurr, Randall Q.; Hupp, Joseph T.; Farha, Omar K.
<x xml:space="preserve">Abstract</x> Here we show a new design strategy for capturing CO2 in nanoporous adsorbents involving 'complementary organic motifs' (COMs) with a precise alignment of charge densities that is complementary to the CO2 quadrupole.